2013
DOI: 10.5539/gjhs.v6n1p107
|View full text |Cite
|
Sign up to set email alerts
|

Rabies and Dog Bites Cases in Lagos State Nigeria: A Prevalence and Retrospective Studies (2006-2011)

Abstract: This study was carried out to determine the prevalence of rabies antigen in brain of dogs slaughtered for consumption and those that died in veterinary clinics as well as to obtain a 6-year retrospective data on dog bites/suspected dog rabies cases in Lagos State. Dog brain samples were collected from dog slaughter slabs and veterinary clinics (for dogs that died in clinics) across the Lagos state while data for retrospective studies (2006-2011) of dog bite/suspected rabies cases were collected from public (go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 31 publications
4
30
1
1
Order By: Relevance
“…As a central state of Nigeria, Plateau State has flourishing commercial dog markets (captured stray dogs are sold), dogs from different states and other neighboring countries (Niger and Chad) are sold to traders from different states of Nigeria (Sabo et al, 2008). The occurrence of apparently healthy dogs with rabies virus in the brain tissues, yet not showing clinical signs of rabies may be more widespread than previously envisaged as rabies antigens were also found in the brain tissues of apparently healthy dogs slaughtered for human consumption in Borno, Benue, Plateau, Katsina and Sokoto, Kaduna, Cross River and Lagos State (Ajayi et al, 2006;Akombo, 2009;Sabo, 2009, Garba et al, 2010Odeh et al, 2013;Isek, 2013;Hambolu et al, 2013). The need to safe guard the health of the people by reducing the rabies risk of exposure warrants continued surveillance.…”
Section: Introductionmentioning
confidence: 97%
“…As a central state of Nigeria, Plateau State has flourishing commercial dog markets (captured stray dogs are sold), dogs from different states and other neighboring countries (Niger and Chad) are sold to traders from different states of Nigeria (Sabo et al, 2008). The occurrence of apparently healthy dogs with rabies virus in the brain tissues, yet not showing clinical signs of rabies may be more widespread than previously envisaged as rabies antigens were also found in the brain tissues of apparently healthy dogs slaughtered for human consumption in Borno, Benue, Plateau, Katsina and Sokoto, Kaduna, Cross River and Lagos State (Ajayi et al, 2006;Akombo, 2009;Sabo, 2009, Garba et al, 2010Odeh et al, 2013;Isek, 2013;Hambolu et al, 2013). The need to safe guard the health of the people by reducing the rabies risk of exposure warrants continued surveillance.…”
Section: Introductionmentioning
confidence: 97%
“…They were of the opinion that majority of the offending dogs were not vaccinated against the disease, but if previously vaccinated, owners fail to revaccinate following expiration of previous vaccination. Hambolu et al [10] reported a decline and general inadequate vaccination of dogs in Lagos State, south-western Nigeria. This further points to the dangers dogs and humans in the community face.…”
Section: Discussionmentioning
confidence: 99%
“…Some workers have reported the problems of vaccine purity and immunogenic inadequacies in the vaccines circulated in Nigeria (Adeyemi et al [14]) and problems of vaccination booster by owners of dogs Hambolu et al [10]. Prevention is said to be cheaper and better than cure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations